Kajian Pustaka: Moderasi Beragama Dalam Konteks Pendidikan Islam Di Era Digital - Yanti Yanti; Yulianto Nur Cahyono; Aida Hayani (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This study aims to identify the challenges and opportunities in teaching religious moderation within the context of Islamic education in the digital era through in-depth literature analysis. The digital era has transformed the landscape of Islamic education, bringing significant changes in how the younger generation accesses and interacts with religious information and values. The primary objective of this study is to understand the state of Islamic education and the impact of the digital era on it, as well as to identify strategies for promoting religious moderation amidst these changes. This study utilizes a comprehensive literature analysis method. The authors explore various literature sources related to religious moderation, Islamic education, and digital technology. The authors identify the key challenges and opportunities that arise in teaching religious moderation in the digital era. The results of this research are that the digital era holds significant potential for facilitating more interactive and engaging religious education. However, there are also serious challenges that must be addressed, such as technology misuse, the dissemination of unverified information, and the risk of online extremism. In conclusion, this study provides insights into the complexity of teaching religious moderation in the digital era. By understanding these challenges and opportunities, Islamic education can take concrete steps to maximize the benefits of digital technology in supporting the understanding and practice of religious moderation among the younger generation.